2009
DOI: 10.4103/1596-3519.55756
|View full text |Cite
|
Sign up to set email alerts
|

Transmission dynamics of malaria in four selected ecological zones of Nigeria in the rainy season

Abstract: Background:Two of the problems of malaria parasite vector control in Nigeria are the diversity of Anopheline vectors and large size of the country. Anopheline distribution and transmission dynamics of malaria were therefore compared between four ecotypes in Nigeria during the rainy season. Methods: Polymerase chain reaction (PCR) was used in molecular identification after morphological identification microscopically. Enzyme linked immunorsorbent assay (ELISA) was used for the blood meal analysis and sporozoite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 20 publications
2
31
1
Order By: Relevance
“…[27][28][29][30][31] Although some studies report zoophily in Afro-tropical vector populations, [5][6][7] we did not detect such behaviors. This may be because of the scarcity of non-human hosts in collection sites that results from an observed lack of animal husbandry practices in Equatorial Guinea relative to other sub-Saharan African localities.…”
contrasting
confidence: 76%
“…[27][28][29][30][31] Although some studies report zoophily in Afro-tropical vector populations, [5][6][7] we did not detect such behaviors. This may be because of the scarcity of non-human hosts in collection sites that results from an observed lack of animal husbandry practices in Equatorial Guinea relative to other sub-Saharan African localities.…”
contrasting
confidence: 76%
“…In a related study, 83.52% P. falciparum sporozoite infection rate was recorded for A. gambiae (Ndiath et al, 2011). The high P. falciparum sporozoite rates shows that the A. gambiae complex members are prominent and potent P. falciparum vectors in South-Western Nigeria and similar report was given by Gilles and Coetzee (1987), Annon (2003), Okwa et al (2007) and Okwa et al (2008). The identified members of the A. gambiae complex, A. gambiae sensu stricto and A. arabiensis, as similarly reported by Okwa et al (2008) and Obembe and Awopetu (2014), are the major P. falciparum vectors in South-Western Nigeria.…”
Section: Discussionsupporting
confidence: 60%
“…Hence, the high P. falciparum sporozoite infection rates for A. gambiae recorded in all the study areas in this study justify the reports from other studies that A. gambiae is highly infective in southwestern Nigeria (Okwa et al, 2007) and it is a prominent malaria vector in Nigeria (Annon, 2003;Gilles and Coetzee, 1987). It has also been reported that A. gambiae is the most prominent malaria vector of P. falciparum, the mosquito species with the highest sporozoite rate and the most infected mosquitoes in the rain forest zone, south-west, of Nigeria (Okwa et al, 2008). The fact that the infective and refractory strains of A. gambiae (sensu stricto) had the same polytene chromosome banding patterns showed that the infective and refractory strains cannot be distinguished using their polytene chromosome banding patterns/photomaps.…”
Section: Discussionmentioning
confidence: 99%